Blueprint : EZNow (Counterless) / Muhammad Hazwan Hariz Mohd Shupian ... [et al.] - Mohd Shupian, Muhammad Hazwan Hariz; Mohd Zaidi, Mohamad Nurifaizal; Hamdan, Harith Farhan; Mohd Safri, Norshazmira; Zabidi, Nor Azwa (2019)
EZNow Company is a business consists of five business partners which are general manager, administrative manager, marketing manager, programmer and financial manager. Our business will be located at Jalan Sultan Azlan Shah, Jalan Ipoh, 51200 Kuala Lumpur, Wilayah Persekutuan Kuala Lumpur. The purpose of our product is to make our business of EZNow all through worldwide because the application had never been made in the market but for now, we are focusing the product in Malaysia. EzNow is an application that can replace counter at the store or in another word, counter less. The application EZNow create are one of the alternative ways that can give benefit both the customer and the company. Our application produced with an easy way which only have 4 features in the application which are profile, scanner, receipt and help.